GOCE in orbita - Bernardini, Fabrizio (GEOmedia, 2009)
GOCE in orbit GOCE (Gravity field and steady-state Ocean Circulation Explorer) is finally in orbit. On March 17th after a few slight problems during the preparatory phases, the mission was successfully launched from the Plesetsk cosmodrome. This article features a focus on one of GOCE's more sophisticated instruments - the Electrostatic gravity Gradiometer or EGG - explained in detail using an image gallery.